Fabrication of Core-Shell Fe3O4@C@MnO2 Microspheres and Their Application in Supercapacitors. Issue 2 (23rd January 2018) - Li, Zhikai; Yao, Ye; Zheng, Yujie; Gao, Tingting; Liu, Zuohua; Zhou, Guowei
Abstract : Core-shell Fe3 O4 @C@MnO2 microspheres were fabricated using multi-step solution-phase interface deposition. Fe3 O4 nanoparticles were coated with SiO2 via the Stöber method and further covered with resorcinol and formaldehyde (RF) resins. Fe3 O4 @C nanoparticles with inter-lamellar void were obtained by carbonizing RF under N2, and etching SiO2 with NaOH. These nanoparticles served as template and were further coated with MnO2 shell to prepare Fe3 O4 @C@MnO2 microspheres. The resultant composites showed a typical core-shell structure with distinct magnetite core, 10 nm inter-lamellar void, a 30 nm thick carbon layer in the middle layer, and a 50 nm thick MnO2 shell at the outer layer. Fe3 O4 @C@MnO2 microspheres served as supercapacitor electrode materials. The electrochemical performance of the Fe3 O4 @C@MnO2 electrode was investigated using cyclic voltammetry, electrochemical impedance spectroscopy, and galvanostatic charge-discharge. Fe3 O4 @C@MnO2 electrode showed a specific capacitance of 158 F g −1 at 0.5 A g −1 and outstanding cycle stability with 89.7% capacitance retention after 2000 cycles. By contrast, the specific capacitance of Fe3 O4 @C electrode was 117 F g −1 at 0.5 A g −1 exhibited and only 75.2% capacitance retention after 2000 cycles. Thus, Fe3 O4 @C@MnO2 microspheres had great potential in supercapacitor applications in the future.